Reflective Supervision Models in School Counseling: A Narrative Review of Approaches and Outcomes - Maya Masyita Suherman; Agus Taufik; Dona Fitri Annisa (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2025)
Reflective supervision has emerged as a critical component in the professional development of school counselors, yet a comprehensive synthesis of existing models and their outcomes remains limited. Purpose: This narrative review aims to identify and analyze various reflective supervision models used in school counseling contexts and examine their reported impacts on counselors' professional growth. Methods: A narrative review methodology was employed, analyzing articles published between 2018 and 2024 from Google Scholar and ERIC databases. Search terms included "reflective supervision," "school counseling," "clinical supervision," and "counselor development." Results: Analysis of 22 relevant studies revealed three predominant supervision models: (1) the Developmental Model, (2) the Competency-Based Model, and (3) the Reflective Practice Model. Common elements across models included structured reflection sessions, collaborative feedback, and relationship-focused approaches. Reported outcomes encompassed enhanced self-efficacy, reduced burnout, improved counseling competencies, and increased job satisfaction among school counselors. Conclusion: Reflective supervision, when implemented through structured models, significantly contributes to the professional growth of school counselors. The findings suggest the need for context-adapted models, particularly in educational settings with limited supervisory resources. This review provides a foundation for developing culturally responsive supervision frameworks in diverse school contexts.